Renin-angiotensin-aldosterone system in climacteric women with arterial hypertension. Antihypertensive therapy features - A. E. Bragina; Yu. N. Salimzhanova; E. Yu. Panfilova; I. G. Fomina (Кардиоваскулярная терапия и профилактика)
The article contains literature review on arterial hypertension (AH) pathogenesis in climacteric women, and the role of humoral systems, in particular, renin-angiotensin-aldosterone system, in AH development among these patients. Pathogenetic features of antihypertensive therapy in climacteric women are discussed.